2021
DOI: 10.1111/bcp.14801
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in pharmacometrics: Opportunities and challenges

Abstract: The explosive growth in medical devices, imaging and diagnostics, computing, and communication and information technologies in drug development and healthcare has created an ever-expanding data landscape that the pharmacometrics (PMX) research community must now traverse. The tools of machine learning (ML) have emerged as a powerful computational approach in other data-rich disciplines but its effective utilization in the pharmaceutical sciences and PMX modelling is in its infancy. ML-based methods can complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 155 publications
0
62
0
Order By: Relevance
“…Applications of ML to MIPD to date have found that ML models are often able to accurately estimate past drug exposure 24,25 , predict future drug exposure 26-28 or select doses [29][30][31][32] . However, the improvement in accuracy from these earlier approaches comes at the expense of pharmacological interpretability and the ability to simulate patient response to alternative dosing regimens 24,33,34 . An advantage of the combination of ML and PK models as described here is that clinical decision making is augmented by ML while maintaining the ability to forecast patient PK and extract mechanistic insight from PK parameter estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of ML to MIPD to date have found that ML models are often able to accurately estimate past drug exposure 24,25 , predict future drug exposure 26-28 or select doses [29][30][31][32] . However, the improvement in accuracy from these earlier approaches comes at the expense of pharmacological interpretability and the ability to simulate patient response to alternative dosing regimens 24,33,34 . An advantage of the combination of ML and PK models as described here is that clinical decision making is augmented by ML while maintaining the ability to forecast patient PK and extract mechanistic insight from PK parameter estimates.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 , 31 , 32 However, the improvement in accuracy from these earlier approaches comes at the expense of pharmacological interpretability and the ability to simulate patient response to alternative dosing regimens. 24 , 33 , 34 An advantage of the combination of ML and PK models as described here is that clinical decision making is augmented by ML while maintaining the ability to forecast patient PKs and extract mechanistic insight from PK parameter estimates. Improving predictive performance for patients with unusual PKs by allowing more flexibility in individual PK parameters has been proposed before.…”
Section: Discussionmentioning
confidence: 99%
“…artificial intelligence can serve as a "computational bridge between big data and pharmacometrics," with specific applications towards TDM (e.g., pharmacokinetics/pharmacodynamics and dose optimization) (McComb et al, 2021). Development of tools that allow clinicians to input individual patient characteristics to predict their SSRI concentration comparable to current pharmacokinetic modeling could overcome some barriers of TDM for SSRIs (e.g., the need for phlebotomy, long turnaround times for assays).…”
Section: Future Directionsmentioning
confidence: 99%
“…They are used for text completion in emails 7 and autonomously driving cars 8 and have even been introduced in the discovery of new antibiotics 9 . Although ANNs have not yet been widely adopted in clinical pharmacology and pharmacometrics, multiple publications point to their potential to become an important tool in these subject areas as well 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…9 Although ANNs have not yet been widely adopted in clinical pharmacology and pharmacometrics, multiple publications point to their potential to become an important tool in these subject areas as well. [10][11][12] In this article, we introduce the concept of ANNs to pharmacometricians, highlight their capability for concentration-time curve predictions, and discuss their differences and limitations compared with classical methods.…”
Section: Introductionmentioning
confidence: 99%